Synthesis, antifungal evaluation and optical properties of silver molybdate microcrystals in different solvents: a combined experimental and theoretical study - Fabbro, Maria T.; Foggi, Camila C. [UNESP]; Santos, Luis P. S.; Gracia, Lourdes; Perrin, Andre; Perrin, Christiane; Vergani, Carlos E. [UNESP]; Machado, Ana L. [UNESP]; Andres, Juan; Cordoncillo, Eloisa; Longo, Elson [UNESP] (Royal Soc Chemistry, 2016)
In this study, we investigate the structure, antifungal activity, and optical properties of beta-Ag2MoO4 using experimental and theoretical approaches. beta-Ag2MoO4 samples were prepared by a co-precipitation method using different solvents (water, ethanol and ammonia), and their antifungal activity against Candida albicans was investigated. The samples were characterized by X-ray diffraction, micro-Raman spectroscopy, field emission scanning electron microscopy, and transmission electron microscopy with energy dispersive spectroscopy. The optical properties were investigated by UV-Vis spectroscopy and photoluminescence measurements at room temperature. The thermodynamic equilibrium shape of the beta-Ag2MoO4 crystals was determined based on the surface energies calculated using Wulff construction. The (011) orientation was the predominant surface in the morphology. The experimental morphology was obtained by varying the surface energy ratio for each facet. A large decrease in surface energy for the (111) surface provided the experimental morphology for crystals synthesized using water and ethanol as solvents; when the surface energies for both (011) and (001) surfaces increased, the crystal morphology obtained using ammonia as a solvent was reproduced. A correlation between the exposed surfaces and antifungal activity was revealed, and an explanation to this behavior that arises from different morphologies and structural data was provided. Theoretical calculations confirm the rationality of the experimental scheme and elucidate the underlying reason for the fungistatic and fungicidal activity against Candida albicans.